2004
DOI: 10.1177/000331970405500107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Peripheral Arterial Disease and Related Risk Factors in an Urban Mexican Population

Abstract: Peripheral arterial disease (PAD) is a growing and often underdiagnosed health problem that predicts cardiovascular events and mortality. Estimating its prevalence in the general population is a major issue for assessing health needs and planning health services. The aim of this study was to determine the prevalence of PAD and its risk factors in an urban Mexican population. A random sample of 400 adult subjects was selected from a Family Medical Unit of the Mexican Institute of the Social Security. Clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
(8 reference statements)
1
4
0
4
Order By: Relevance
“…The data was not statistically significant (p=0.5). This is in concordance with the study done by Eason SL et al, 20 Buitrón LV et al 21 which showed that the presence of either signs or symptoms was more frequent in subjects with PAD.…”
Section: Abpi Value Cases Controlssupporting
confidence: 93%
See 1 more Smart Citation
“…The data was not statistically significant (p=0.5). This is in concordance with the study done by Eason SL et al, 20 Buitrón LV et al 21 which showed that the presence of either signs or symptoms was more frequent in subjects with PAD.…”
Section: Abpi Value Cases Controlssupporting
confidence: 93%
“…23 Buitrón-Granados LV et al studied prevalence of peripheral arterial disease and related risk factors in an urban Mexican population. 21 They included 400 adult subjects and finally concluded that serum triglycerides ≥150mg/dL was one of the risk factors related to PAD.…”
Section: Abpi Value Cases Controlsmentioning
confidence: 99%
“…Data sources for ABI: urban China [67], urban Mexico [68], South Africa [28], southeast Spain [69], Sweden (Sigvant Birgitta pers comm), Thailand [70], United States [9]. Hypertension data for the same countries come from the World Health Organization Global Infobase, http://www.who.int/infobase/report.aspx.…”
Section: Resultsmentioning
confidence: 99%
“…7 Reported prevalences of PAD range from 4% to 27%. [8][9][10] Data on PAD in the Thai population are scarce. Up to now there has been no population-based study published on the prevalence of PAD in Thailand.…”
mentioning
confidence: 99%